2021
DOI: 10.1144/sp511-2020-46
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic and sedimentological aspects of the worldwide distribution of Apectodinium in Paleocene/Eocene Thermal Maximum deposits

Abstract: The Paleocene/Eocene Thermal Maximum (PETM) is characterized by pronounced global warming and associated environmental changes. In the more-or-less two decades since prior regional syntheses of Apectodinium distribution at the PETM, extensive biological and geochemical datasets have elucidated the effect of rising world temperatures on climate and the biome. A Carbon Isotope Excursion (CIE) that marks the Paleocene/Eocene Boundary (PEB) is associated with an acme of marine dinocysts of the genus Apectodinium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 198 publications
2
5
0
Order By: Relevance
“…Similar transitions from terrestrial to brackish deposits in conjunction with the PETM at the southern edge of the North Sea Basin were also reported from other sites, such as Cobham in southeastern England (Collinson et al, 2003) and the Oise region in France (Cavagnetto, 2000;Nel et al, 1999;Dupuy et al, 2014). Therefore, our carbon isotope record is consistent with peat formation during the onset of the PETM and widespread inundation of coastal lowlands due to sea level rise during a later stage of the PETM (see, e.g., Denison, 2021).…”
Section: Cie 1 (Petm)supporting
confidence: 82%
See 1 more Smart Citation
“…Similar transitions from terrestrial to brackish deposits in conjunction with the PETM at the southern edge of the North Sea Basin were also reported from other sites, such as Cobham in southeastern England (Collinson et al, 2003) and the Oise region in France (Cavagnetto, 2000;Nel et al, 1999;Dupuy et al, 2014). Therefore, our carbon isotope record is consistent with peat formation during the onset of the PETM and widespread inundation of coastal lowlands due to sea level rise during a later stage of the PETM (see, e.g., Denison, 2021).…”
Section: Cie 1 (Petm)supporting
confidence: 82%
“…Most likely, admixture of marine organic matter more depleted in 13 C compared to terrestrial organic matter prevented the full recovery to δ 13 C TOC values as high as those recorded in the purely terrestrial organic matter of the Main Seam. However, the shift from the negative peak of δ 13 C TOC values at the top of the Main Seam to increasing values in the interbed at or near the lithological boundary has to be treated with caution since the PETM-driven transgression in this coastal setting may have led to a hiatus at the top of the Main Seam (Denison, 2021) that obscured an even more negative shift of δ 13 C TOC values.…”
Section: Cie 1 (Petm)mentioning
confidence: 99%
“…Jolley et al (2021) demonstrated that the PETM predated subaerial exposure and the formation of the Flett unconformity in the FSB in the same way as the PETM predates the Y1 subaerial unconformity in the Froan Basin. Since the PETM is considered a regional datum (Denison, 2021), this comparison shows that there was no delayed transient uplift in the Froan Basin compared to the FSB. Within the resolution of biostratigraphic data, it appears that maximum uplift and subaerial exposure was broadly time equivalent across the region.…”
Section: Stratigraphic Expression Of Regional Uplift-a North Atlantic...mentioning
confidence: 97%
“…The marine biotic response to the climatic warming event of the PETM is well documented in localities worldwide (e.g., Thomas and Shakleton, 1996;Kahn and Aubry, 2004;Crouch et al, 2001;Sluijs et al, 2007a;Denison, 2021) and in the GOM, where it is reflected in assemblage changes or turnover in specific groups of single-celled planktonic organisms, most notably marine dinoflagellates, benthic foraminifera, and calcareous nannoplankton. Interpreting the deepwater GOM record at any single location may be complicated by a limited recovery of calcareous microfossils, but distinct trends noted in wells across the basin and in the Anchor 3 core suggest that multiple factors played a role in calcareous and organic fossil abundances.…”
Section: Biotic Expression Paleocene-eocene Boundary Interval Deepwat...mentioning
confidence: 99%